2D Silicon‐Based Semiconductor Si2Te3 toward Broadband Photodetection. Issue 13 (3rd March 2021) - Chen, Jiawang; Tan, Chaoyang; Li, Gang; Chen, Lijie; Zhang, Hanlin; Yin, Shiqi; Li, Ming; Li, Liang; Li, Guanghai
Abstract: Silicon‐based semiconductor materials dominate modern technology for more than half a century with extraordinary electrical‐optical performance and mutual processing compatibility. Now, 2D materials have rapidly established themselves as prospective candidates for the next‐generation semiconductor industry because of their novel properties. Considering chemical and processing compatibility, silicon‐based 2D materials possess significant advantages in integrating with silicon. Here, a systematic study is reported on the structural, electrical, and optical performance of silicon telluride (Si2 Te3 ) 2D material, a IV−VI silicon‐based semiconductor with a layered structure. The ultrawide photoluminescence (PL) spectra in the range of 550–1050 nm reveals the intrinsic defects in Si2 Te3 . The Si2 Te3 ‐based field‐effect transistors (FETs) and photodetectors show a typical p‐type behavior and a remarkable broadband spectral response in the range of 405–1064 nm. Notably, the photoresponsivity and detectivity of the photodetector device with 13.5 nm in thickness and upon 405 nm illumination can reach up to 65 A W −1 and 2.81 × 10 12 Jones, respectively, outperforming many traditional broadband photodetectors. It is believed this work will excite interests in further exploring the practical application of 2D silicon‐based materials in the field of optoelectronics. Abstract : A 2D silicon‐based photodetector based on Si2 Te3 with broad spectrum response is introduced. The intrinsic defects in Si2 Te3 are revealed through ultrawide photoluminescence spectra in the range of 550–1050 nm. A remarkable broadband spectral response from 405 to 1064 nm and a photoresponsivity up to 65 A W −1 is realized in Si2 Te3 ‐based photodetectors.